2015
DOI: 10.3109/19401736.2015.1101589
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitogenome of Amolops loloensis and related phylogenetic relationship among Ranidae

Abstract: Rufous-spotted Torrent Frog (Amolops loloensis) is a vulnerable species, which belongs to the family Ranidae and is distributed in high-gradient streams of Sichuan and Yunnan, China. In this study, we first determined the complete mitochondrial DNA sequence of A. loloensis (GenBank accession no. KT750963). The mitogenome sequence of A. loloensis was 18 926 bp in size. It contained 13 protein-coding genes (PCGs), two rRNAs, 22 tRNAs, and a D-loop region. Amolops loloensis shared the same gene arrangement patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
3
9
0
Order By: Relevance
“…Compared with reported ranid frogs, the location of replication origin (O L ) in A. chunganensis mitogenome was rearranged. This gene order was consistent with other reported Amolops species (Zhang, Xia & Zeng, 2016; Xue et al, 2015; Xia et al, 2014). The O L is located in the tRNA genes cluster “WANCY”.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Compared with reported ranid frogs, the location of replication origin (O L ) in A. chunganensis mitogenome was rearranged. This gene order was consistent with other reported Amolops species (Zhang, Xia & Zeng, 2016; Xue et al, 2015; Xia et al, 2014). The O L is located in the tRNA genes cluster “WANCY”.…”
Section: Resultssupporting
confidence: 92%
“…It is similar to A. mantzorum and A. loloensis gene arrangement pattern (Shan et al, 2016; Xue et al, 2015). Interestingly, a trnK pseudogene was located between cox2 and atp8 genes (Fig.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The genus Amolops is distributed across Nepal, northern India, western and southern China to Malaya and contains 58 species (Frost 2019). Recently, some mitochondrial genomes of genus Amolops have been reported that the tRNA gene cluster, 'WANCY', as a hotspot of mtDNA rearrangement, and it has provided evidence of rearrangements between species within the genus (Huang et al 2014;Shan et al 2016;Xue et al 2016;Zhang et al 2016). But the phylogenetic relationship of these species still remains controversial.…”
mentioning
confidence: 99%